An Examination of the Effects of Online Marketing Strategies on Consumer Purchase Intentions - Ridwan Ridwan (Greenation Management and Business Review, 2024)
The internet has become a necessary component of daily life in our digital age, especially for those in the business sector. This has prompted the development of numerous internet marketing techniques that businesses employ to connect with customers. This study aims to investigate how online marketing tactics affect customer purchase decisions. Quantitative research methodologies are used in this work. Customers that make online purchases of goods or services make up the study population. Using a random sampling technique, 200 consumers made up the research sample. The SPSS software is then used to examine the data that has been gathered. The findings demonstrated the influence of internet marketing tactics on customer purchase decisions. Consequently, businesses must be aware of the internet marketing techniques employed to consumers and increase sales.